Missing expectations: Windlass tourniquet use without formal training yields poor results. Issue 5 (November 2019) - Dennis, Andrew; Bajani, Francesco; Schlanser, Victoria; Tatebe, Leah C.; Impens, Ann; Ivkovic, Katarina; Li, Anqi; Pickett, Thomas; Butler, Caroline; Kaminsky, Matthew; Messer, Thomas; Starr, Frederic; et al.
Abstract : BACKGROUND: Despite significant attempts to educate civilians in hemorrhage control, the majority remain untrained. We sought to determine if laypersons can successfully apply one of three commercially available tourniquets; including those endorsed by the United States Military and the American College of Surgeons. METHODS: Preclinical graduate health science students were randomly assigned a commercially available windless tourniquet: SAM XT, Combat Application Tourniquet (CAT), or Special Operation Forces Tactical Tourniquet (SOFT-T). Each was given up to 1 minute to read package instructions and asked to apply it to the HapMed Leg Tourniquet Trainer. Estimated blood loss was measured until successful hemostatic pressure was achieved or simulated death occurred from exsanguination. Simulation survival, time to read instructions and stop bleeding, tourniquet pressure, and blood loss were analyzed. RESULTS: Of the 150 students recruited, 55, 46, and 49 were randomized to the SAM XT, CAT, SOFT-T, respectively. Mean overall simulation survival was less than 66% (65%, 72%, 61%; p = 0.55). Of survivors, all three tourniquets performed similarly in median pressure applied (319, 315, and 329 mm Hg; p = 0.54) and median time to stop bleeding (91, 70, 77 seconds; p = 0.28). There was a statistical difference in median blood loss volume favoring SOFT-T (SAM XT, 686 mL; CAT, 624 mL; SOFT-T, 433 mL; p = 0.03). All 16 participants with previous experience were able to successfully place the tourniquet compared with 81 (62%) of 131 first-time users ( p = 0.008). CONCLUSION: No one should die of extremity hemorrhage, and civilians are our first line of defense. We demonstrate that when an untrained layperson is handed a commonly accepted tourniquet, failure is unacceptably high. Current devices are not intuitive and require training beyond the enclosed instructions. Plans to further evaluate this cohort after formal "Stop the Bleed" training are underway.